Proceedings of the 1994 International Symposium on Software Testing and Analysis - ISSTA '94 1994
DOI: 10.1145/186258.187153
|View full text |Cite
|
Sign up to set email alerts
|

Protocol testing

Abstract: Communication protocols are the rules that govern the communication between the different components within a distributed computer system. Since protocols are implemented in software and/or hardware, the question arises whether the existing hardware and software testing methods would be adequate for the testing of communication protocols. The purpose of this paper is to explain in which way the problem of testing protocol implementations is different from the usual problem of software testing. We review the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(12 citation statements)
references
References 38 publications
(9 reference statements)
0
6
0
6
Order By: Relevance
“…It focuses on test sequence generation methods, test coverage, fault models and prediction, test tools, and experience reports. (Bochmann and Petrenko, 1994) provide a good overview of methods and their relevance for software testing. (Sidhu and Leung, 1989) give four formal methods for protocol testing by developing test sequences.…”
Section: Related Workmentioning
confidence: 99%
“…It focuses on test sequence generation methods, test coverage, fault models and prediction, test tools, and experience reports. (Bochmann and Petrenko, 1994) provide a good overview of methods and their relevance for software testing. (Sidhu and Leung, 1989) give four formal methods for protocol testing by developing test sequences.…”
Section: Related Workmentioning
confidence: 99%
“…A detailed overview of automata-based testing methods can be found in a number of articles, e.g. [BP94], [SL1989]. Any of these automata-based testing methods are demanding a minimal, complete finite state-machine.…”
Section: Related Workmentioning
confidence: 99%
“…Finite-state machines (FSMs) are commonly used for specifying reactive systems due to its simplicity and precise definition of the temporal ordering of interactions [5]. From the two traditional Moore/Mealy FSMs models it is found that in the Mealy machines, since the outputs are associated with the transitions, some behaviors can be implemented with fewer states than Moore machines.…”
Section: Fsmsmentioning
confidence: 99%